2022
DOI: 10.3389/fcimb.2022.1057668
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal cancer and bacterial part of gut microbiota – A multidisciplinary point of view

Abstract: There is an urgent need to search for new screening methods that allow early detection of esophageal cancer and thus achieve better clinical outcomes. Nowadays, it is known that the esophagus is not a sterile part of the gastrointestinal tract. It is colonized with various microorganisms therefore a “healthy” esophageal microbiome exists. The dysbiotic changes of esophageal microbiome can lead to the development of esophageal diseases including esophageal cancer. There is a strong consensus in the literature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“… 65 Augmented COX-2 expression, Toll-like receptor activation, and the effects of secreted metabolites are additional potential conduits through which F. nucleatum exerts its influence on esophageal cancer. 125 In a 2023 study, Ding et al reported that F. nucleatum infection led to an increase in the concentration of compounds such as putrescine and spermine, which are known to have favorable effects on the metastasis of ESCC. 66 Moreover, nascent evidence suggests a plausible association between the presence of F. nucleatum and ESCC metastasis, although the precise underlying mechanisms necessitate further elucidation.…”
Section: F Nucleatum and Tumorigenesis Tumor Metastasismentioning
confidence: 99%
“… 65 Augmented COX-2 expression, Toll-like receptor activation, and the effects of secreted metabolites are additional potential conduits through which F. nucleatum exerts its influence on esophageal cancer. 125 In a 2023 study, Ding et al reported that F. nucleatum infection led to an increase in the concentration of compounds such as putrescine and spermine, which are known to have favorable effects on the metastasis of ESCC. 66 Moreover, nascent evidence suggests a plausible association between the presence of F. nucleatum and ESCC metastasis, although the precise underlying mechanisms necessitate further elucidation.…”
Section: F Nucleatum and Tumorigenesis Tumor Metastasismentioning
confidence: 99%
“…[ 17 ]. Recent studies suggest an association between ESCC and increased oral abundance of Firmicutes , Prevotella, Streptococcus , and Porphyromonas , as well as a decrease in Proteobacteria , Neisseriales, Lautropia, Bulleidia, Catonella, Corynebacterium, Moryella, Peptococcus , and Cardiobacterium [ 18 , 19 , 20 , 21 , 22 ]. Similar but distinct changes have been observed in EAC, where Tannerella forsythia was associated with higher risk, while depletion of Neisseria and Streptococcus pneumoniae was associated with lower risk [ 22 , 23 ].…”
Section: Tumor and Host Microbiome On The Pathogenesis Of Ec And Gcmentioning
confidence: 99%
“…The abundance, heterogeneity, and precise constitution of microbiota across various organs could potentially influence the pathogenesis of EC. Multiple research endeavors have posited that an imbalance within the gut microbial ecosystem, termed dysbiosis, could be implicated in the initiation and progression of esophageal neoplasia [17][18][19][20][21][22][23]. Individuals exhibiting reduced microbial richness in the esophagus and diminished salivary microbial diversity in China might be at an augmented risk of developing esophageal squamous dysplasia (a precursor to EC) and EC, correspondingly [24,25].…”
Section: Introductionmentioning
confidence: 99%